Augmented Reality-Based Programming Using Atmega 2560 Microcontroller Trainer Kit Support. - Satrinawati Satrinawati; Dedy Irfan; Efrizon Efrizon (Jurnal Teknologi Informasi dan Pendidikan, 2022)
The application of an augmented reality system to the Atmega 2560 microcontroller trainer kit is a tool designed to create learning methods that are interactive, fun, motivating, and provide space for students to develop creativity and independence. This research uses research and development (R&D) methods. This research and development consists of a preliminary study stage, needs analysis, design, manufacture, testing of tool specifications and the final stage is product evaluation with expert opinion. The development of this microcontroller trainer kit has three main parts, namely the microprocessor, input and output. The microcontroller used is the ATmega 2560. By using augmented reality technology and adding electronic components such as DC motors, servo motors, ultrasonic sensors, this tool can be used in sensor and transducer learning. Apart from learning sensors, this trainer kit can also be applied to learning microcontrollers and their applications. This trainer kit is equipped with a practicum module as a support in learning. Through the microcontroller trainer kit and Augmented reality system, it is hoped that student competency will be better.